AKTIVITAS ANTIOKSIDAN PADA FORMULA TABLET TERIPANG KELING (Holothuria atra) - Ahmad Fauzan Lubis; Sri Purwaningsih; Kustiariyah Tarman (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
This study about activity of antioxidant aimed to determine the chemical characterization of sandfish, sandfish meat and sandfish powder, determine the best formulation in manufacturing Holothuria atra tablet based on DEPKES RI standard and to determine the antioxidant activity and the active compounds that act as antioxidants in the extract of Holothuria atra tablets. The method used in the manufacture of tablets is the direct compression method using 6 formulations to treat the kind of powder substance that is the ingredient of sandfish are intact and substances from the meat of sandfish. Tablet chosen based on the standards of the Ministry of Health that includes the physical characteristics of the test tablet and shelf-life stability. Tablet rivet sandfishtested the antioxidant activity by the method of 2,2-diphenyl-1-picrylhydrazyl (DPPH). Tests to determine the active compounds that act as antioxidants with thin layer chromatography (TLC) and bioautography antioxidants and also to determine the functional groups using analysis of Fourier Transform Infrared (FTIR). The yield of sandfish powder is considerably low. Yield of sandfish powder are 10.26% and sandfish meat powder are 9,82%. The protein content of sandfish powder are 60,89% lower compared to sandfish meat powders of 63,57%. Formula elected from the sandfish tablet test based on physical characteristics and stability test of the shelf life of the tablet is the formula A2 with the composition of the powder formulation Holothuria atra (25%), Ac-Di-Sol (2%), L-HPC (2%), Aspartame (0.5%), menthol (0.2%), talk (1%), magnesium stearate (1%) and lactose: mannitol (67.8%) and has antioxidant activity with IC50 value of 97.22 ppm. TLC test and Bio-autography showed that the class of antioxidant compounds are steroid, and suspected compounds at FTIR test, that act as antioxidants compound has similarities to the sterol class.